Systematic Evaluation of Managed Pressure Drilling Variants: A Framework-Based Comparative Review for Operational Decision Support (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
MPD has evolved from a niche technique into a mainstream drilling capability over the last decade. It is now used in HPHT, deepwater, unconventional tight-gas, and sour-gas reservoirs. Despite this widespread adoption, the operational question of which MPD variant is best suited to a particular well profile has historically been addressed in the published literature on a case-by-case basis, without structured comparative synthesis. This paper addresses that gap through a systematic framework-based evaluation of fourteen MPD case-study publications sourced from the SPE and IADC literature between 2015 and 2025. A six-dimensional analytical framework, inductively developed from the recurring performance themes within the corpus, serves as the uniform evaluative instrument. The six dimensions encompass: well-control sensitivity and detection thresholds; narrow-margin pressure window navigation; non-productive time (NPT) and invisible lost-time reduction; rate-of-penetration (ROP) enhancement relative to conventional baselines; cementing and tripping operational reliability; and economic performance across deployment contexts. Synthesis findings confirm that MPD delivers well-control detection sensitivity approximately one to two orders of magnitude superior to conventional pit-volume methods; that variant selection materially affects operational outcomes; that NPT reduction is robustly demonstrated while ROP enhancement evidence remains comparatively sparse; and that economic viability is strongly contingent on multi-well campaign scale. A structured application-domain selection map, matching ten canonical operational situations to corpus-preferred MPD variants across three evidence-calibrated confidence tiers, is presented as the primary decision-support contribution of this review.